2018
DOI: 10.1021/acs.jmedchem.8b00103
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Based Discovery and Optimization of Benzo[d]isoxazole Derivatives as Potent and Selective BET Inhibitors for Potential Treatment of Castration-Resistant Prostate Cancer (CRPC)

Abstract: The bromodomain and extra-terminal (BET) family proteins have gained increasing interest as drug targets for treatment of castration-resistant prostate cancer (CRPC). Here, we describe the design, optimization, and evaluation of benzo[ d]isoxazole-containing compounds as potent BET bromodomain inhibitors. Cocrystal structures of the representative inhibitors in complex with BRD4(1) provided solid structural basis for compound optimization. The two most potent compounds, 6i (Y06036) and 7m (Y06137), bound to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 38 publications
1
47
1
Order By: Relevance
“…Moreover, nonpolar interactions were found between BRD4 hydrophobic residues (Trp 81, Leu 92, Leu 94, Cys 136, and Ile 146) and the inhibitor's nonpolar groups (as shown in Figure 2). These interaction patterns have been confirmed by MD simulations analysis, as shown later in Tables 2 and 3, in addition to confirming with other experimental studies, 51–55 which indicated the accuracy and reliability of the docking results. For better understanding, the general scheme and 3D‐structure for the interaction between BRD4 and C1 inhibitor were depicted in Figure 3.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…Moreover, nonpolar interactions were found between BRD4 hydrophobic residues (Trp 81, Leu 92, Leu 94, Cys 136, and Ile 146) and the inhibitor's nonpolar groups (as shown in Figure 2). These interaction patterns have been confirmed by MD simulations analysis, as shown later in Tables 2 and 3, in addition to confirming with other experimental studies, 51–55 which indicated the accuracy and reliability of the docking results. For better understanding, the general scheme and 3D‐structure for the interaction between BRD4 and C1 inhibitor were depicted in Figure 3.…”
Section: Resultssupporting
confidence: 87%
“…The structure of BRD4 protein was obtained from RCSB protein database (PDB ID: 5Y8W) with 1.76 Å resolution 51 . After the preparation of initial BRD4 structures, including removing heteroatoms and cryptographic water molecules, a staged minimization was performed on the protein structure using Tripos forcefield and Powell method, implemented in SYBYL‐X v2.1 software 56,57 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, Xu's group described a series of benzo[d] isoxazole-containing compounds as potent Brd4 inhibitors. 58 Among them, compounds 41 and 42 showed the highest binding affinities to Brd4 1 , TGI values of 70% and 51% were achieved, respectively.…”
Section: Brd4 Inhibitorsmentioning
confidence: 91%